Networks of Production and Dissemination of Information on Education in Latin America and the Caribbean: Their Usefulness for Decision Makers - Téllez, Francisco (Education Policy Analysis Archives, 2008)
This article presents the results of a study that explored the formal and informal information networks operating in Latin America and the Caribbean, and estimated their utility for educational policymaking processes. To achieve this goal the following procedures were undertaken: first, a search for information networks in the region was conducted; second, an analysis matrix for information networks intended to reveal their main characteristics (origin, members, information resources provided, types of information offered and topics for which information is provided, among others) was made; and third, interviews to key informants about the utility of these networks to design educational policies in the region were conducted. The main conclusions of the study were: a) most of the information related to educational policy that circulates through information networks in Latin America and the Caribbean is not useful for policymaking processes; b) the networks that offer analytic abstracts of research and policy experiences, and propose policy solutions for policy problems in a non-technical language increase the possibility of information use by policymakers; c) informal networks, where consultants, advisors, or colleagues communicate orally to policymakers relevant information about the characteristics of successful policy initiatives in specific contexts, seem to have more impact than formal networks on policy development; and d) the utility of information networks for educational policy decisions is related to their ability to communicate, in a clear and straightforward way, the main results of policy researches and experiences.